2015
DOI: 10.1097/mao.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Visual Vertical Tilt Attraction to the Side of Rod Presentation

Abstract: These effects suggest that short-term visual memory and multisensory cortical processing interfere with SVV measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…This phenomenon is probably related to short-term visual memory and similar to visual dependency at rod-and-frame test. We defined the effect as visual attraction, and showed that it was higher in children, teenagers, and senior patients in comparison to middle-aged adults (10). We also observed a higher attraction in women versus men.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…This phenomenon is probably related to short-term visual memory and similar to visual dependency at rod-and-frame test. We defined the effect as visual attraction, and showed that it was higher in children, teenagers, and senior patients in comparison to middle-aged adults (10). We also observed a higher attraction in women versus men.…”
mentioning
confidence: 61%
“…In a previous study, we showed that VVS was attracted to the side of bar presentation and this effect varied with age and sex (10). This phenomenon is probably related to short-term visual memory and similar to visual dependency at rod-and-frame test.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…As such, the rod was initially presented either approximately horizontal or slightly sloped to either left or right of the horizontal line. The initial orientation was ran domly sampled from the following set of angles: ±45 o , ±55 o , ±65 o , ±75 o and ±85 o as the rod presentation can impact results as well (Toupet, Van Nechel & Grayeli, 2015).…”
Section: Methodsmentioning
confidence: 99%